If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6xy + -2x = 0 Reorder the terms: -2x + 6xy = 0 Solving -2x + 6xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '2x'. 2x(-1 + 3y) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1 + 3y)' equal to zero and attempt to solve: Simplifying -1 + 3y = 0 Solving -1 + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 3y = 0 + 1 3y = 0 + 1 Combine like terms: 0 + 1 = 1 3y = 1 Add '-3y' to each side of the equation. 3y + -3y = 1 + -3y Combine like terms: 3y + -3y = 0 0 = 1 + -3y Simplifying 0 = 1 + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 3/2x-1 | | 5v=3v+18 | | p/-25-650 | | 5t-8=14+16-9 | | d+e+e+d+d+d+e+d= | | -5y+3(y+4)=30 | | 5v=3e+18 | | p-3/5p=20 | | 12y^2+2y-2= | | 5x+6(x-8)= | | 128+2x= | | 7y=y+36 | | 4y+-6=-2+8y | | 2/3x=5=-11 | | (6x-1)/2-(2x+1)/3=5 | | -14+30=-4(x+2) | | 8g=3g+15 | | 8x+x=r | | 6x+42=9x-3 | | 4e=2e+14 | | y^2+x+y=0 | | -64/16 | | 10k-3/-3 | | 400= | | 4y-6=-2+8y | | 2k-3/-3 | | x+y-250=687 | | x+7-150=357 | | x=100+-1y | | 22=4y-10 | | 3x+14=-7 | | -8z-2z=8z+3-5z |